Forcing a square into a circle: why South Africa’s draft revised material transfer agreement is not fit for purpose - Esselaar, Paul; Swales, Lee; Bellengère, Devarasi; Mhlongo, Banele; Thaldar, Donrich (Frontiers in Pharmacology, 2024)
The South African National Health Research Ethics Council (NHREC) recently released a final draft revision of the standard material transfer agreement (MTA) that was promulgated into law in 2018. This new draft MTA raises pertinent questions about the NHREC's mandate, the way in which the draft MTA deals with data and with human biological material, and its avoidance of the concept of ownership. After South Africa's data protection legislation, the Protection of Personal Information Act (POPIA), became operational in mid 2021, the legal landscape changed and it is doubtful that the NHREC has a residual mandate to govern personal information in health research. Furthermore, data is dealt with in a superficial, throw-away fashion in the draft MTA. The position with human biological material is not substantially better, as the draft MTA fails to recognise that human biological material can contain pathogens, which has important legal and ethical ramifications that are not sufficiently addressed. A central problem with the draft MTA is its use of the term 'steward', and avoidance of the legal concept of 'ownership'. This is not only misaligned with the South African legal framework, but also fails to consider the ethical case for recognising ownership. Finally, a call to embrace decolonial thinking in health research underscores the importance of recognising ownership in order to foster the growth of the local bio-economy. Key recommendations to reshape the draft MTA include: Making use of the eventual revised MTA optional, and allowing it to evolve with input from scientific and legal communities; regulating the transfer of associated data in a separate data transfer agreement that can be incorporated by reference in the MTA; enhancing guidance on liability and risk management in respect of human biological material that contains pathogens; and, finally, adopting a decolonial approach in health research governance, which requires recognising the ownership rights of South African research institutions.